Josquin des Prez - Lowinsky, Edward E. 1908-1985; Blackburn, Bonnie J. (London Oxford university press, 1976)
This volume constitutes the report of the 1971 International Josquin Festival Conference held at the Julliard School of Music in New York City. The papers assembled this collection are an elegant tribute to the study of Josquin and address biographical information, source studies, style and analysis, studies on genres, individual works, performance practice, performance and interpretation, and problems in editing Josquin's music.